Networking by numbers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Networking is largely lived, not learned, or at least not taught. But some basics of networking between organisations can be shared, and in two-week training sessions in June, a good three dozen agricultural policy makers from eastern and southern...